2000
DOI: 10.1084/jem.191.7.1095
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor–Related Apoptosis-Inducing Ligand (Trail) Is an Inhibitor of Autoimmune Inflammation and Cell Cycle Progression

Abstract: The tumor necrosis factor–related apoptosis-inducing ligand (TRAIL) induces apoptosis of tumor cells but not normal cells; its role in normal nontransformed tissues is unknown. We report here that chronic blockade of TRAIL in mice exacerbated autoimmune arthritis, and that intraarticular TRAIL gene transfer ameliorated the disease. In vivo, TRAIL blockade led to profound hyperproliferation of synovial cells and arthritogenic lymphocytes and heightened the production of cytokines and autoantibodies. In vitro, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
265
3
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(288 citation statements)
references
References 44 publications
(68 reference statements)
16
265
3
4
Order By: Relevance
“…Furthermore, the decoy receptor, TRAIL R3, was present on CD14ϩ RA SF MNCs. In contrast to our data, TRAIL overexpression ameliorated CIA (8), suggesting that cells from the mouse joint express TRAIL R1 or R2 (8). Further, TRAIL-null mice exhibited increased CIA compared with control mice (9).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the decoy receptor, TRAIL R3, was present on CD14ϩ RA SF MNCs. In contrast to our data, TRAIL overexpression ameliorated CIA (8), suggesting that cells from the mouse joint express TRAIL R1 or R2 (8). Further, TRAIL-null mice exhibited increased CIA compared with control mice (9).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to Fas/Fas ligand (FasL)-induced cell death, TRAIL induces apoptosis only in tumor or tumor-like cells but not in normal cells (6), although one study showed that TRAIL ligation activates apoptosis in normal hepatocytes (7). Nonetheless, overexpression of TRAIL ameliorated, while the injection of soluble TRAIL R2 exacerbated, experimental arthritis in mice (8). Moreover, TRAIL-null mice are more susceptible to collagen-induced arthritis (CIA) (9), suggesting that TRAIL may have a potential therapeutic role in RA.…”
mentioning
confidence: 99%
“…Several observations suggest that targeting TRAIL or its death receptors may have a therapeutic role in RA: an anti-DR5 monoclonal antibody (mAb) prevents erosive arthritis in a murine xenograft model for human RA (8), TRAIL-null mice have an increased susceptibility to collagen-induced arthritis (CIA) (9), and chronic blockade of TRAIL in mice with CIA exacerbated arthritis, while intraarticular TRAIL gene transfer ameliorated the disease (10). Administration of TRAIL in humans has raised concerns with regard to the outcome, such as the potential for hepatotoxicity (11) and unpredictable effects that would depend on the expression levels of different TRAIL receptors (6)(7)(8).…”
mentioning
confidence: 99%
“…TRAIL and its receptors have been identified as one of the three deathreceptor/ligand systems (FasL and TNF-a being the others) that regulate intercellular apoptosis in the immune system (Wu, 2009). In fact, in different systems, TRAIL was shown to have a huge variety of effects, between immunosuppression, immunoregulation, pro-or antiviral action, and tumor immunosurveillance (Lunemann et al, 2002, Song et al, 2000.…”
Section: Innate and Adaptive Immune Systemsmentioning
confidence: 99%
“…While TRAIL -/-and TRAIL-R -/-mice do not spontaneously develop autoimmunity, treatment of autoimmune diseases with TRAIL has been successful in several animal models (Falschlehner et al, 2009). In one study, gene transfer of TRAIL prevented collagen-induced arthritis, while blocking TRAIL led to an increase in severity (Song et al, 2000). In another arthritis study, mice receiving collagen-treated TRAIL-expressing DCs had diminished joint inflammation compared with controls.…”
Section: Trail and Autoimmunitymentioning
confidence: 99%